2004
DOI: 10.1007/bf03018403
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the fetus and newborn of maternal analgesia and anesthesia: a review

Abstract: P Pu ur rp po os se e: : To review the effects of maternal anesthesia and analgesia on the fetus and newborn.M Me et th ho od ds s: : An on-line computerized search of Medline, Embase, and the Cochrane Collaboration via PubMed was conducted. English language articles were selected. The bibliographies of relevant articles and additional material from other published sources were retrieved and reviewed.P Pr ri in nc ci ip pa al l f fi in nd di in ng gs s: : No one test clearly separates the effects on the fetus/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 167 publications
0
52
0
11
Order By: Relevance
“…One of the parents' first responsibilities is giving informed consent (or refusal) for medical procedures that may impact the health of their infant. Mothers should ask questions and weigh the risks and benefits of any drug that is to be administered (Lang, Geldner, & Wulf, 2003;Littleford, 2004).…”
Section: Implications For Childbirth Educatorsmentioning
confidence: 99%
“…One of the parents' first responsibilities is giving informed consent (or refusal) for medical procedures that may impact the health of their infant. Mothers should ask questions and weigh the risks and benefits of any drug that is to be administered (Lang, Geldner, & Wulf, 2003;Littleford, 2004).…”
Section: Implications For Childbirth Educatorsmentioning
confidence: 99%
“…However, recent literatures show that despite the high prevalence of maternal hypotension, term infants can tolerate this placental blood perfusion challenge without any major negative consequences 28 . Meanwhile, a range of studies also have not found any sequel from the fluid interventions in patients undergoing Cesarean section with neuraxial blockade 27,29,30 . Our results are consistent with these findings, where fluid preloading produced little effect on infants' Apgar and neurobehavioral assessment scorings, as well as on the arterial umbilical-cord pH values.…”
Section: Discussionmentioning
confidence: 99%
“…While analysis of umbilical cord blood gases remains the gold standard for assessment of the newborn, [28] assessment of all the newborn in this study was also carried out using the Apgar [29] scoring system. In our study, the mean umbilical cord venous blood pH was 7.35±0.05 and that of the arterial blood pH was 7.28±0.05.…”
Section: Discussionmentioning
confidence: 99%